Relationship between pension plans and corporate governance : evidence from S&P 500 companies - Lim, Sharon Mei Ling (2008)
This paper investigates the relationship between Defined Benefit pension plans and corporate governance using sample from S&P 500. The corporate governance attributes used include board leadership, board composition and ownership structure. For the first part of our study, we examine the relationship between discount rate, expected rate of return and funding status with corporate governance. For the second part of our study, we investigate the relationship between Tobin’s Q with deficit of funding status (internal debt level) and external debt level of the company. Our results show that better corporate governance has contributed to the underfunding of pension plans and that companies choose to allocate their resources to more profitable investments rather than pension plans.